AI VS. DEMOCRACY: PRESENT AND POSSIBLE FUTURES - Damnjanović, Ivana (Serbian political thought, 2025)
The aim of this paper is to explore and systematize current research on the relationship between artificial intelligence (AI) and democracy, primarily focusing on existing AI applications, in order to understand the general avenues of exploration conceived within the field of political science on this topic, and to evaluate their results so far. However, some thought will also be given to the more far-fetched possibilities of AI development and their implications for democracy. Using Robert Dahl’s theory of democracy, the paper outlines why the AI is perceived as a threat to liberal democracy, especially in regard to principles of equality, personal autonomy, and autonomous choice, and the functioning of the public sphere. Finally, the paper considers some possible, if not very probable, future developments in AI, namely the inception of artificial general intelligence (AGI) and artificial superintelligence (ASI), and their implications for democracy. While existing AI applications do seem to erode certain preconditions for functioning democracy, it is nevertheless possible to overturn this trend by restructuring AI development based on the democratic debate and participatory design.